2018
DOI: 10.1016/j.conbuildmat.2017.10.105
|View full text |Cite
|
Sign up to set email alerts
|

Use of recycled fillers in bituminous mixtures for road pavements

Abstract: This paper reports the results of a laboratory investigation on the use of recycled fillers in bituminous mixtures for road pavements. The fillers were obtained by crushing and sieving (0.00-0.063 mm) Stabilized Bottom Ashes from municipal waste incinerators and Electric Arc Furnace Steel Slags. Moreover, a currently used calcareous filler was included in the research for comparative purposes. Two filler dosages were considered in the experiments. Laboratory tests aimed at investigating compaction properties, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Consequently, new techniques and research have developed to use the CDW as a NA replacement [8][9][10][11][12][13][14][15][16][17][18][19][20]. Great advantages are obtained from the use of CDW as a partial or total replacement of NA.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, new techniques and research have developed to use the CDW as a NA replacement [8][9][10][11][12][13][14][15][16][17][18][19][20]. Great advantages are obtained from the use of CDW as a partial or total replacement of NA.…”
Section: Introductionmentioning
confidence: 99%
“…AC has been primarily used as a material in constructing road and airport pavements. (Xu, 2010;Romera et al, 2016) and in some cases it is mixed to fibers fillers of reinforcement (Xiong et al, 2015;Topini et al, 2018). The effectiveness of bituminous concrete is strictly influenced by the combination of base binder, additive type and dosage (Moreno-Navarro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The mixture components include coarse aggregates, a high binder content and a high filler content [2]. The most commonly used fillers are crushed stone, cement and lime [4]; however, recycled materials [5], industrial products, waste materials [6] and even polyethylene terephthalate (PET) have also been used [2].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the ductility is related to the type and concentration of the filler. Finally, Topini, Toraldo, Andena and Mariani [5] revised the compaction properties, volumetric characteristics, and mechanical behavior of SMAs; the mechanical behavior was evaluated with the indirect tensile test at different temperatures. For this, they used two types of recycled material used as filler (stabilized bottom ashes and electric arc furnace steel slag), and their results showed that the behavior of these fillers was similar to or better than that of mixtures with a conventional filler.…”
Section: Introductionmentioning
confidence: 99%